Digital Ethics in the Perspective of Islamic Education: Cultivating Religious Awareness in Cyberspace - Lailil Muharromah; Umar Manshur (Al-Qalam Institue, 2025)
This study aims to Islamic religious education in the digital era faces significant challenges due to the rapid development of technology, particularly in ensuring that the content aligns with true Islamic teachings. This study aims to explore the role of digital ethics in raising religious awareness online, particularly in the context of religious education. Using a qualitative approach, the study involved interviews with educators and principals and observations of technology use in Islamic schools and madrasas in Indonesia. Key findings indicate that while technology offers significant opportunities for increasing access to religious learning, oversight of content quality and educators' skills in managing technology remain challenges. Most students have not fully implemented Islamic ethics in their use of social media and digital platforms, while available content often does not align with religious principles. This research contributes to identifying the importance of strengthening an Islamic-based digital curriculum and improving training for educators in managing technology to effectively support religious education.